Implicit and explicit knowledge in second language learning, testing and teaching - Ellis, Rod (Second Language Acquisition., 2009)
The implicit/explicit distinction is central to our understanding of the nature of L2 acquisition. This book begins with an account of how this distinction applies to L2 learning, knowledge and instruction. It then reports a series of studies describing the development of a battery of tests providing relatively discrete measurements of L2 explicit/ implicit knowledge. These tests were then utilized to examine a number of key issues in SLA - the learning difficulty of different grammatical structures, the role of L2 implicit/ explicit knowledge in language proficiency, the relationship between.